Cosmopolitan nationalism in the cases of South Korea, Israel and the U.S. Issue 6 (17th August 2020) - Maxwell, Claire; Yemini, Miri; Engel, Laura; Lee, Moosung
Abstract: In this essay we develop the concept of 'cosmopolitan nationalism', offering a working definition and suggesting ways sociologists of education might draw on it in their future work. We show how it is a useful analytical lens through which to examine contemporary policies and practices that navigate global processes (ranking systems, mobility of people, expectations for futures) but also take account of nationalistic tendencies, as well as local and national attempts to challenge persistent inequalities within education systems. By using policy examples from three countries (South Korea, Israel and the US), we illuminate how cosmopolitan nationalism is evident across various initiatives in these countries, and the varied implications this has for education systems in terms of equality, access and quality.